Gaya Desain Kolonial Belanda dan Cina pada Interior Hotel Ganefo Surabaya - Ivana Novita Santoso; Adi Santosa (Intra, 2013)
Ganefo Hotel was originally a residence of an ex- lieutenant of China who was assigned by the Dutch to oversee the activities of the local population. Although at this time the building has functioned as a hotel, the styles of Dutch Colonial and Chinese are applied to the building is still maintained until now. The combination of styles in this hotel makes it an interesting object to be researched. This study aims to analyze the Dutch Colonial and Chinese styles which still exist in this building. The method used in this study is descriptive qualitative method. The result demonstrates the application of Dutch Colonial design styles and China on the interior Ganefo Hotel Surabaya which is seen on the building orientation, layout, organization of space, space-forming elements, transition elements, furniture, and decorative elements.